KINEMATIC STRUCTURE OF SIDE KICK TECHNIQUE BY RIGHT LEG STARTING FROM FRONT STANCE PERFORMED BY HIGHLY QUALIFIED ATHLETES SPECIALIZING IN HAND-TO-HAND COMBAT - Vako, I. I.; Zhyrnov , O. V.; Levandovska, L. Yu. (Rehabilitation and Recreation, 2023)
The aim is to analyze the kinematic structure of side kick technique by the right leg starting from the front stance by highly qualified athletes specializing in hand-to-hand combat. Research methods. To fulfil the set tasks, particular research methods were used, namely, analysis of scientific and methodological literature sources and documentary materials, methods of registration and analysis of athlete movements (“Qualisys Motion Capture”, a system of video recording and analysis of athlete’s movements and 3D registration of human movements). The research findings were processed using the methods of mathematical statistics. We registered the technique of performing the studied motor action by 12 highly qualified athletes. Results. The analysis of the kinematic structure of side kick technique by the right leg starting from the front stance (like most kicks) consists of 7 phases: the phase of preparation for the kick, the phase of encroachment, the double-support phase, the phase of the striking/kicking movement, contact phase, the phase of returning of the kicking leg to the support, and phases of returning to fighting stance. All the studied phases of the kick can be generally divided into two periods, i.e., the period of active actions, which consists of the following phases: preparation for the kick, encroachment, the double-support phase, kicking movement, contact; and the period of return to the initial position (fighting stance). The total duration of technique performance is 1.83 s, the duration of the active period is 0.84 s, and the period of return to the initial position is 0.99 s, respectively. Thus, the duration of the active period is 45.9% of the total duration of technique performance, and the period of return to the original position comprises 54.1%, respectively. That is, the duration of the period of return to the original position is almost 10% longer within the total duration of technique performance. Sufficiently long duration of the kick execution, 1.83 s, and the return to the initial position of 0.99 s determine the specificity of this action application during the match. The movement indicators of the kicking biolink (the one of right tibial joint) were analyzed. It was established that the shape of the trajectory has only a slight curvature, especially when viewed from the side, and the shape of the trajectory when viewed from above is S-shaped, with a slight curvature. Conclusions. It was determined that the side kick by the left leg starting from the front stance is performed by highly qualified athletes specializing in hand-to-hand combat with high efficiency.